Distinct patterns of the histone marks associated with recruitment of the methionine chain-elongation pathway from leucine biosynthesis - Xue, Ming (Journal of experimental botany, 2015)
© The Author 2014. Published by Oxford University Press on behalf of the Society for Experimental Biology.